Changes in the South Atlantic Subtropical Gyre circulation from the 20th into the 21st century - Oliveira, Fernanda Marcello de (2017)
Through analysis of large-scale ocean gyre dynamics from simulation results of the ocean component of the Community Earth System Model version 1 - the Parallel Ocean Program version 2 (CESM1-POP2) - this study builds upon existing research suggesting recent changes in the circulation of global subtropical gyres with respect to the South Atlantic Ocean. Results all point to an increase in the total counterclockwise circulation and a southward displacement of the sub- tropical gyre system. The northern boundary of the South Atlantic Subtropical Gyre (SASG) is represented by the bifurcation of the southern branch of the South Equatorial Current (sSEC) into the North Brazil Undercurrent/Current (NBUC/NBC) to the north and the Brazil Current (BC) to the south. The sSEC Bifurcation Latitude (SBL) dictates the partition between waters flowing poleward and those flowing equatorward. Although a northward migration of the SBL would be expected with the gyre spin up and associated poleward transport increase, the SBL migrates southwards at a rate of 0.051o/yr, in conjunction to a substantial increase in the equatorward advection of waters within the sSEC-SBL-NBUC system, which is included in the upper-branch of the Atlantic Meridional Overturning Circulation.